The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1111/dar.12502
|View full text |Cite
|
Sign up to set email alerts
|

Exploring synthetic heroin: Accounts of acetyl fentanyl use from a sample of dually diagnosed drug offenders

Abstract: Introduction and Aims. Acetyl fentanyl, a fentanyl analogue emerging onto the recreational drug scene, has been responsible for numerous recent fatal overdoses in the USA, Europe and Russia. Studies reporting acetyl fentanyl use are presently limited to case studies and mortality reports. This study explores the nature of acetyl fentanyl use through the collection of first-hand qualitative data from users to inform public health and drug control policy responses. Design and Methods. A series of focus group int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(18 citation statements)
references
References 21 publications
1
16
0
1
Order By: Relevance
“…We do not know if these are experimental one-time users or recurrent fentanyl users, nor do we know the reasons why respondents sought fentanyl. However, existing studies and anecdotal reports indicate that fentanyl enables a different drug experience than heroin (Miller, Stogner, Miller, & Blough, 2017). In their qualitative study of persons using heroin in Massachusetts and New Hampshire, Ciccarone and colleagues (2017) found that fentanyl’s intensity and potent ability to surpass heroin tolerance or OAT medicine was appealing to some people.…”
Section: Discussionmentioning
confidence: 99%
“…We do not know if these are experimental one-time users or recurrent fentanyl users, nor do we know the reasons why respondents sought fentanyl. However, existing studies and anecdotal reports indicate that fentanyl enables a different drug experience than heroin (Miller, Stogner, Miller, & Blough, 2017). In their qualitative study of persons using heroin in Massachusetts and New Hampshire, Ciccarone and colleagues (2017) found that fentanyl’s intensity and potent ability to surpass heroin tolerance or OAT medicine was appealing to some people.…”
Section: Discussionmentioning
confidence: 99%
“…Scientific literature reported a mixture of p-fluorofentanyl, alphamethylfentanyl, 3-methylfentanyl, acetyl-fentanyl which may include heroin constituents. [11][12][13][14] The danger related to fentanyl derivatives is due to: 1) the variability of compounds that may exist in a given sample 2) the inconsistency of dosages 3) their potency 4) easy access by consumers through the deep web or black market 14,15 and 5) fatal respiratory depression. In recent years, the great spread of fentanyl-like compounds has created massive problems from social, health, normative and analytical points of view.…”
Section: Introductionmentioning
confidence: 99%
“…However, increasing variability in the evolving supply means that some individuals may be unable to discern fentanyl-adulteration (Amlani et al, 2015; Kenney et al, 2018). Research suggests that the fentanyl-adulteration does result in different intoxication effects in comparison heroin, including: intensity of onset, duration of action, increased overdose risk, and other embodied effects (Carroll et al, 2017; Ciccarone, 2017; Ciccarone et al, 2017; Macmadu et al, 2017; Mars et al, 2018; Miller et al, 2017; Somerville, 2017). As a result, fentanyl-adulteration has implications for overdose response in terms of rapid progression, and atypical physical symptoms (Somerville, 2017).…”
Section: Introductionmentioning
confidence: 99%